Using the Historical Approach for the Analysis of Literature in the EFL Teaching Context - Blanco, Willmen Leonardo (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This article presents an English as a Foreign Language lesson aimed at Venezuelan university students of International Studies. The purpose of the lesson is to guide students towards interpreting a literary text from a Historical Approach perspective. Theoretical principles are analyzed, and the central text is the poem Not My Business by Nigerian writer Niyi Osundare. The poem’s theme is considered relevant for the target population as it addresses abandonment and indifference in the face of social and political injustice. A lesson was implemented based on the poem, which not only facilitated language development and communicative competence but also promoted reflection on the consequences of apathy towards social issues. Thanks to an eclectic, student-centered approach, the selected text served as an example of how to narratively recount past events in a meaningful way, addressing a topic of notable relevance.